2012
DOI: 10.1016/j.molimm.2012.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA-15a in autoantibody production in interferon-augmented murine model of lupus

Abstract: MicroRNAs (miRNAs) are involved in the regulation of immunity via targeting of mRNA encoding immune response elements. In this report, alterations in the expression of microRNAs as autoantibody levels increase was investigated. The (NZB X NZW) F1 or B/W mouse model of systemic lupus erythematosus (SLE) naturally has increased autoantibodies with aging. IFNalpha (type I IFN) accelerates B/W disease, however, the effects of a related IFN, IFNlambda, which is a type III IFN, is largely unknown. The purpose of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 71 publications
0
25
0
1
Order By: Relevance
“…96 ), all pathogenetic modes of mirs regulation of iFN type i expression require further study. Whereas iFN type i has been established as the main contributor to sle pathogenesis 97 , it is not surprising that the expression of mir-146a in pBmcs of sle patients negatively correlates with disease activity and severity of renal involvement 94,98 . The other cells of innate immunity, macrophages, display deregulated phenotypes and functions in sle patients.…”
Section: Innate Immunity and Mirs And Slementioning
confidence: 99%
“…96 ), all pathogenetic modes of mirs regulation of iFN type i expression require further study. Whereas iFN type i has been established as the main contributor to sle pathogenesis 97 , it is not surprising that the expression of mir-146a in pBmcs of sle patients negatively correlates with disease activity and severity of renal involvement 94,98 . The other cells of innate immunity, macrophages, display deregulated phenotypes and functions in sle patients.…”
Section: Innate Immunity and Mirs And Slementioning
confidence: 99%
“…IFN treatment elevated miR-15a levels, which in turn correlated with lower levels of regulatory B cell subpopulations, particularly B-10. The authors concluded that IFN-induced miR-15a overexpression may have a specific negative regulatory effect on this B cell subpopulation [19]. …”
Section: Pathogenesis Of Lupus Nephritismentioning
confidence: 99%
“…Notably, miR-15a was highly expressed in the immunosuppressive B-cell subset (B-10). 38 These results suggest that miR-15a induced a loss of regulatory B cells by targeting the antiapoptotic protein Bcl-2, which in turn led to enhanced autoantibody production by autoreactive B cells. 38 The most common genomic aberration in B-cell chronic lymphocytic leukemia is the deletion of the human chromosomal region 13q14, corresponding to the mouse chromosomal region 14qC3, which harbors the miR-15a/miR-16-1 cluster.…”
Section: Fas/faddmentioning
confidence: 80%
“…38 These results suggest that miR-15a induced a loss of regulatory B cells by targeting the antiapoptotic protein Bcl-2, which in turn led to enhanced autoantibody production by autoreactive B cells. 38 The most common genomic aberration in B-cell chronic lymphocytic leukemia is the deletion of the human chromosomal region 13q14, corresponding to the mouse chromosomal region 14qC3, which harbors the miR-15a/miR-16-1 cluster. In a recent in vivo mouse study, the loss of the miR-15a/16-1 cluster was shown to accelerate the proliferation of B lymphocytes, resulting in a B-cell autonomous lymphoproliferative disorder.…”
Section: Fas/faddmentioning
confidence: 80%